Quantitative Trait Loci for Cold Tolerance in Chickpea. Issue 2 (1st March 2019) - Mugabe, Deus; Coyne, Clarice J.; Piaskowski, Julia; Zheng, Ping; Ma, Yu; Landry, Erik; McGee, Rebecca; Main, Doreen; Vandemark, George; Zhang, Hongbin; Abbo, Shahal
Abstract : Fall‐sown chickpea ( Cicer arietinum L.) yields are often double those of spring‐sown chickpea in regions with Mediterranean climates that have mild winters. However, winter kill can limit the productivity of fall‐sown chickpea. Developing cold‐tolerant chickpea would allow the expansion of the current geographic range where chickpea is grown and also improve productivity. The objective of this study was to identify the quantitative trait loci (QTL) associated with cold tolerance in chickpea. An interspecific recombinant inbred line population of 129 lines derived from a cross between ICC 4958, a cold‐sensitive desi type ( C. arietinum ), and PI 489777, a cold‐tolerant wild relative ( C. reticulatum Ladiz), was used in this study. The population was phenotyped for cold tolerance in the field over four field seasons (September 2011–March 2015) and under controlled conditions two times. The population was genotyped using genotyping‐by‐sequencing, and an interspecific genetic linkage map consisting of 747 single nucleotide polymorphism (SNP) markers, spanning a distance of 393.7 cM, was developed. Three significant QTL were found on linkage groups (LGs) 1B, 3, and 8. The QTL on LGs 3 and 8 were consistently detected in six environments with logarithm of odds score ranges of 5.16 to 15.11 and 5.68 to 23.96, respectively. The QTL CT Ca‐3.1 explained 7.15 to 34.6% of the phenotypic variance in all environments, whereas QTL CT Ca‐8.1 explained 11.5 to 48.4%. The QTL‐associated SNP markers may become useful for breeding with further fine mapping for increasing cold tolerance in domestic chickpea.